Memorandum of Agreement between Universiti Teknologi MARA (UiTM) and Mae Fah Luang University (MFU) on UiTM-MFU international matching grant entitled "Are key audit matters valued by investors? Evidence from Malaysia and Thailand" - UiTM, Cawangan Kelantan (2022)
This Memorandum of Agreement (hereinafter referred to as "MoA") is made on 02 November 2022 between Universiti Teknologi MARA (hereinafter referred to as "UiTM"), a public university established under the Universiti Teknologi MARA Act 1976 (Act 173) whose address is at 40450 Shah Alam, Selangor, Malaysia and shall include its lawful representatives and permitted assigns and Mae Fah Luang University (hereinafter referred to as 'MFU'), a public university, under the Royal Charter, with generous support from the Royal Thai Government, whose address is at 333 Moo1, Thasud, Muang, Chiang Rai 57100 Thailand and shall include its lawful representatives and permitted assigns. (UiTM and MFU hereinafter referred to singularly as "Party" and collectively as "Parties')